Clinical and logistical factors in aeromedical dispatch: A retrospective study of helicopters rescues - Bottega, Francesca; Gambolò, Luca; Mina, Andrea; Filetici, Luca; Cipolotti, Giovanni; Ruberti, Serena; Giupponi, Angelo (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: One of the main reasons for healthcare professionals to intervene with a patient engaged in sports activities is trauma. In the case of severe traumas or incidents that occur in hard-to-reach locations, the preferred method of transport is aeromedical evacuation. Unfortunately, there is limited published evidence regarding this subject. Therefore, an epidemiological analysis was conducted to understand the primary cause of dispatching medical transport to mountainous regions, whether due to clinical or logistical factors. Methods: A retrospective observational analysis was conducted using the HEMS database from 1/1/2009 to 12/31/2018. The database collected interventions carried out through aeromedical services in the regions of Lombardy, Veneto, and Trentino-Alto Adige. Results: 31,063 missions were recorded, comprising 14,155 (45.5%) cases related to patients experiencing acute medical issues and 11,717 (37.7%) related to traumatic events. The remaining 5,191 (16.7%) missions did not have a clearly defined primary reason for dispatch. Among the individuals involved in traumatic incidents, 6,123 (19.7%) were engaged in sporting activities. Concerning patients affected by acute medical events, 2,787 (8.9%) individuals were engaged in sports. Conclusions: Age influences the type of sporting activity requiring aeromedical rescue. In numerous instances, the predominant sporting activities are associated with challenging terrains (such as skiing and hiking), underscoring the significance of logistical Additionally, it is noted that the aircraft is deployed for patients with unstable clinical conditions in approximately half of the cases. Therefore, transportation may have an impact on the clinical picture.